Improvement in seed germination potential and adaptability of vegetable soybean (Glycine max l. Merr.): Improvement in seed germination potential and adaptability of vegetable soybean (Glycine max l. Merr.) - M K KUCHLAN,; P KUCHLAN,; M SRIVASTAVA , (Journal of Oilseeds Research, 2023)
The germination problem in vegetable soybean variety Karune is most limiting factor for its wide spread cultivation. The problem of inherent germination problem was aimed to eradicate by developing segregating vegetable soybean line with high germination potential by crossing with EC 538828 which is yellow bold seeded with better germination with rapid seed feeling rate and resistance to several diseases. 14 out of 460 segregating lines were vegetable type with green seed, sweet taste, high germination potential and resistance to major diseases.